2015
DOI: 10.1016/s2215-0366(15)00168-6
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported depression measures in cancer: a meta-review

Abstract: SummaryDepression measurement in cancer care is complex and inconsistent. It is difficult for investigators to select the best-performing tool. We conducted a meta-review to integrate the findings of reviews of patient-report depression measures used as screeners or case-finders in oncology. We searched Medline, PsycINFO, EMBASE and grey literature from 1999-2014. We identified 19 reviews representing 372 primary studies assessing more than 50 depression measures. We used 11 highquality reviews to guide our an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…Six reviews (three high quality) including 27 articles examined the relationship between chronic illness (including asthma and cancer) and school interpersonal relationships, such as those between peers and teachers (Vance & Eiser ; Gurney et al ; Basch ; Herrmann et al ; Pini et al ; Wakefield et al ). Twenty original articles, the majority of which were qualitative research, indicated that chronic illness may be associated with poorer school relationships compared with students without chronic illness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six reviews (three high quality) including 27 articles examined the relationship between chronic illness (including asthma and cancer) and school interpersonal relationships, such as those between peers and teachers (Vance & Eiser ; Gurney et al ; Basch ; Herrmann et al ; Pini et al ; Wakefield et al ). Twenty original articles, the majority of which were qualitative research, indicated that chronic illness may be associated with poorer school relationships compared with students without chronic illness.…”
Section: Resultsmentioning
confidence: 99%
“…Half of the reviews were not systematic, limiting the reliability of the findings. Only two systematic reviews received PRISMA scores of 20 or above, a threshold previously used to categorize reviews as ‘high quality’ (Willis & Quigley ; Wakefield et al ). Few reviews presented data on risk of bias, summary measures or methods of data handling.…”
Section: Discussionmentioning
confidence: 99%
“…The most often used questionnaires measuring depression in cancer patients are the Hospital Anxiety and Depression Scale HADS [ 7 ], the Beck Depression Inventory BDI [ 8 ] and the Center for Epidemiologic Studies Depression Scale CES-D [ 9 ], for a new summarizing review cf. [ 10 ]. A further, freely available and more recently developed questionnaire is the Patient Health Questionnaire PHQ-9 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…While individual settings may take for granted that one approach has been determined to be optimal, the literature is mixed at best and clear guidelines on which approach to use do not exist. Many cancer settings and psycho-oncology researchers, for example, continue to opt for screening measures that exclude somatic symptoms despite equivocal findings (i.e., the Hospital Anxiety and Depression Scale [5]; [1113]), and the potential to “miss” patients with clinically significant depressive symptoms. The current study compares three of the most widely recognized approaches to depression assessment among medically ill patients, inclusive, exclusive, and substitutive, in a large sample of ambulatory cancer patients.…”
Section: Introductionmentioning
confidence: 99%